Redesign BOH Tea Packaging Design - Nor Ziratul Aqma, Norzaman; Muhammad Firdhaus, Che Hassan (2013)
Tea is considered as the second most consumed beverage in the world. Some even described tea as the world’s favourite drink. There are various kinds of tea brands in the supermarket. Based on preliminary research done at Giant, Jusco, Tesco and Carrefour within Klang Valley, results show that the teabag type of packaging has the highest percentage offered, and BOH dominates the Malaysian market. Even though BOH is the largest tea manufacturer in Malaysia, and claims to be the number one preferred brand, but it does not portray any Malaysian image in its design; in terms of the colour used, neither the structure design nor the graphic in its packaging. In order to validate or to support previous statements, a comparative study on the current trend of tea packaging design in the Malaysian market was carried out. Visual analysis is the best method in identifying the importance of the origin branding in creating good brand identity. Imagery is really important since it can reflect the origin of the product and a powerful tool in brand communication. Identifying the appropriate image for BOH packaging design is crucial. The survey was done by distributing sets of questionnaires among randomly selected respondents. Open ended questions were constructed in order to collect as many as possible of their preferences and point of views about Malaysia. From the study, results show that Kuala Lumpur City Centre (KLCC) is the best icon that represents Malaysia since it already has an established name globally. Lastly, incorporating the proposed image in the new look of BOH tea bag type of packaging design was done. Hopefully by using the KLCC image it will enhance the market performance locally as well as internationally. Not only that, this study can be used as guidelines in designing packaging design especially for learning purposes